An ADAM17-Neutralizing Antibody Reduces Inflammation and Mortality While Increasing Viral Burden in a COVID-19 Mouse Model - Hedges, Jodi F.; Snyder, Deann T.; Robison, Amanda; Grifka-Walk, Heather M.; Blackwell, Karlin; Shepardson, Kelly; Kominsky, Douglas; Rynda-Apple, Agnieszka; Walcheck, Bruce; Jutila, Mark A. (Frontiers in Immunology, 2022)
Angiotensin Converting Enzyme 2 (ACE2) is the primary cell entry receptor for SARS-CoV and SARS-CoV-2 viruses. A disintegrin and metalloproteinase 17 (ADAM17) is a protease that cleaves ectodomains of transmembrane proteins, including that of ACE2 and the proinflammatory cytokine TNF-alpha, from cell surfaces upon cellular activation. We hypothesized that blockade of ADAM17 activity would alter COVID-19 pathogenesis. To assess this pathway, we blocked the function of ADAM17 using the monoclonal antibody MEDI3622 in the K18-hACE2 transgenic mouse model of COVID-19. Antibody-treated mice were healthier, less moribund, and had significantly lower lung inflammation than saline-treated mice. However, the viral burden in the lungs of MEDI3622-treated mice was significantly increased. Thus, ADAM17 appears to have a critical anti-viral role, but also may promote inflammatory damage. Since the inflammatory cascade is ultimately the reason for adverse outcomes in COVID-19 patients, there may be a therapeutic application for the MEDI3622 antibody.